Helyi termék értékesítésének online kihívásai a Vajdaságban - Nagyné Molnár, Melinda; Kápolnai, Zsombor (Közép-Európai Közlemények, 2024)
Vajdaság is one of the most developed agricultural regions in Serbia. Agriculture has a long history in its territory, thanks to the region’s favorable conditions. In 2014, the so-called Agricultural and Rural Development Strategy was launched in the country, the aim of which is to adapt the agricultural and rural development practices of the EU. In the process, many reforms were implemented. This is also the case with support for short supply chains. According to the 2022 data register of the Vajdaság Agricultural Association, 325 local producers and local product makers are registered in the region. Our goal was to find out what criteria form the buyer side of the producer circle, what they buy, how they want to get information about the local product range. The questionnaire survey was also stimulated by the fact that VASZ (Vajdaság Agrarian Association) operating in Vajdaság, recognizing the connections between REL and local economic development, took an active role in initiating the creation of a new website that could help customers to get information about registered products, and their availability. The same interface would give the producers the opportunity to gain recognition and get to know each other. This is also of great importance because, in the long term, it can serve well to bring together those who offer local products3 and also to build a community identity across borders. In the long term, the collaboration can create shopping communities that are already well known in Hungary but do not yet exist in Serbia, which can help create a relationship between producers and consumers with marketing and communication tools, can help display the offer, and can even function as a sales channel maintainer (webshop, producer’s market and shop), which in turn can serve to improve the prospects of local producers/product makers living in Vajdaság4